Composing the Filipino music transculturation and hybridity in nineteenth century urban colonial Manila (1858-1898) - Chua, Maria Alexandra Iñigo; Buenconsejo, Jose S. (Quezon City College of Music, University of the Philippines Diliman, 2017)
The study, utilizing printed and published music anthologies, piano sheets and notated music in travel books and newspapers, seeks to understand the process of musical transculturation that negotiated the entanglements of the local with the predominant globalizing ideologies such as capitalism, industrialization, secularism, and later nationalism. It critically assesses the nature of music hybridities in music print capitalism, particularly in church music publications, sheet music of the emerging ilustrado class and the music of Julio Nakpil embodied in political nationalism. This study, therefore, explores the critical effects of colonialism, modernity, and globalization in the development of music in urban colonial Manila. It is in urban cities, as sites of confrontation, that impact of transcultural exchanges is most evident. Hence, the long process of cultural crossing and appropriation that transpired in capital Manila after 1834 was arguably a critical factor that gave rise to a distinctively modern transcultural "Filipino" music. The study is an inaugural undertaking in Philippine musicological studies for it attempts to understand an important, hitherto unexplored, historical area, i.e., music in urban colonial Manila in the age of Philippine modernity (1858-1898). It is also a new approach to music studies in the country, because it explores music as a social material process, specifically its relation to capitalism that was the condition for the creation of a set of transcultural-composed music. Furthermore, it explores the process of the localization of Western musical genres and, conversely, the Westernization of native musical genres. Composing the Filipino is, thus, significant because it can contribute to the current discourse on the formation of Hispanic-influenced, syncretic and hybrid Philippine music in the colonial capital city of Manila.
Thesis (Doctor of Philosophy in Music)--University of the Philippines Diliman
Keywords: Music -- Philippines; Cultural fusion in Music; Composition (Music).; National socialism and musicology -- Philippines